2021
DOI: 10.1016/j.jmmm.2021.168278
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency behavior of laminated electric steel sheet: Investigation of ferromagnetic hysteresis loops and incremental permeability

Abstract: The frequency dependence of ferromagnetic hysteresis and the related core losses is still an open question. From scaling relations up to space discretized and simultaneous contributions resolutions, different levels of accuracy in the estimation of these losses can be reached. Below a given frequency known as the quasi-static threshold, it is well admitted that the hysteresis cycle remains unchanged. A precise evaluation of this threshold is fundamental to simulate and evaluate precisely the magnetization beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…While methods have been proposed for modeling this phenomenon, the resulting models have been rarely validated based on experimental data [41][42]. Past studies have demonstrated that increasing the 𝐻 contribution incrementally during MIP signature measurements while monitoring the eddy current testing (ECT) coil impedance used for implementing the 𝐻 contribution is a good indirect means of observing the accommodation phenomenon [43]. However, the extension of the DF model to account for accommodation phenomena is not explicitly treated in the present study owing to space restrictions.…”
Section: Congruency and The Accommodation Statusmentioning
confidence: 99%
“…While methods have been proposed for modeling this phenomenon, the resulting models have been rarely validated based on experimental data [41][42]. Past studies have demonstrated that increasing the 𝐻 contribution incrementally during MIP signature measurements while monitoring the eddy current testing (ECT) coil impedance used for implementing the 𝐻 contribution is a good indirect means of observing the accommodation phenomenon [43]. However, the extension of the DF model to account for accommodation phenomena is not explicitly treated in the present study owing to space restrictions.…”
Section: Congruency and The Accommodation Statusmentioning
confidence: 99%
“…A. N. Stashkov regarded MIP as indicator of compression stress in low-carbon steel [ 6 ]. Benjamin Ducharne characterized the stress changes in iron–cobalt magnetic sheet based on MIP [ 7 ]. Tetsuya Uchimoto evaluated the creep-induced microstructural changes in 12Cr-Mo-V-W microstructure under different creep test conditions by using the MIP method [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Питомі втрати у магнітопроводі є важливим показником. Зростання магнітних втрат обумовлено насамперед зростанням паразитних вихрових струмів внаслідок порушення міжлистової ізоляції, ослаблення пресування викликає такі негативні явища як підвищення вібрацій окремих вузлів та машини загалом [4,5].…”
unclassified